Does intellectual capital efficiency improve islamic banking performance? The moderating effect of islamic governance - Nasirwan, Nasirwan; Ridha, M. Arsyadi; Juliani, Dian (Universitas Muhammadiyah Yogyakarta, Indonesia, 2024)
Research aims: This paper aims to examine the moderating effect of Islamic governance on the relationship between intellectual capital efficiency (ICE) and Islamic bank performance.Design/Methodology/Approach: The population for this study covered Islamic banks in Indonesia. Purposive sampling was performed, and statistical analysis was conducted using moderating regression analysis by selecting among the common, fixed, and random effects models. The statistical tool utilized was E-Views 12.Research findings: The primary finding of this study is related to the positive moderating effect of structural capital efficiency on the relationship between intellectual capital and Islamic banking performance. Furthermore, Islamic governance could not strengthen the influence of human capital efficiency and capital employed efficiency on the performance of Islamic banks.Theoretical contribution/Originality: To the best of the authors’ knowledge, no other research has examined whether intellectual capital significantly affects the performance of Islamic banks with a moderating effect on Islamic governance in Indonesia.Practitioner/Policy implication: The results of this research provide input for the Sharia Supervisory Board to pay attention to the management of intellectual capital in Islamic banks and encourage Islamic banks to increase the value of intangible resources, capabilities, and asset knowledge to create and maintain competitive advantages in Islamic banks.Research limitation/Implication: This study focused only on Indonesian Islamic banks; hence, future research should be extended to Islamic insurance and microfinance.